2016
DOI: 10.1016/j.psyneuen.2016.07.216
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal coupling between testosterone and cortisol from adolescence to older adulthood

Abstract: The hypothalamic-pituitary-adrenal (HPA) and hypothalamic-pituitary-gonadal (HPG) axes are typically conceptualized as mutually inhibitory systems; however, previous studies have found evidence for positive within-person associations (i.e., coupling) between cortisol and testosterone. One developmental hypothesis is that positive testosterone-cortisol coupling is unique to the adolescent period and that coupling becomes attenuated, or even switches direction, in adulthood. This study used a lifespan sample (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…A parsimonious explanation of this coupling is that participants found the TSST (or its modification) to invoke a challenge more than a stressor response. Robust coupling across axes fits with the emerging dual-axis models (Marceau et al, 2015; Susman, Peckins, Bowes, & Dorn, 2017; Harden et al, 2016; Juster, Raymond, Desrochers, Lupien, 2016; Stephens, Mahon, McCaul, & Wand, 2016), and with an interpretation of the TSST as both a stressor and a challenge (Mehta, Jones, & Josephs, 2008; Mehta, Welker, Zilioli, & Carre, 2015; Denson, Mehta, & Tan, 2013; Salvador, 2005). It is more difficult to integrate with models that describe inhibition of one axis by the other (Viau, 2002; Koob & LeMoal, 2001), such as studies which describe androgens as a stress buffer, DHEA as an anti-glucocorticoid (Kalimi et al, 1994), or which find unique high testosterone/cortisol reactivity ratio findings (Glenn et al, 2011; Huovinen et al, 2009; Welker et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A parsimonious explanation of this coupling is that participants found the TSST (or its modification) to invoke a challenge more than a stressor response. Robust coupling across axes fits with the emerging dual-axis models (Marceau et al, 2015; Susman, Peckins, Bowes, & Dorn, 2017; Harden et al, 2016; Juster, Raymond, Desrochers, Lupien, 2016; Stephens, Mahon, McCaul, & Wand, 2016), and with an interpretation of the TSST as both a stressor and a challenge (Mehta, Jones, & Josephs, 2008; Mehta, Welker, Zilioli, & Carre, 2015; Denson, Mehta, & Tan, 2013; Salvador, 2005). It is more difficult to integrate with models that describe inhibition of one axis by the other (Viau, 2002; Koob & LeMoal, 2001), such as studies which describe androgens as a stress buffer, DHEA as an anti-glucocorticoid (Kalimi et al, 1994), or which find unique high testosterone/cortisol reactivity ratio findings (Glenn et al, 2011; Huovinen et al, 2009; Welker et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…This dual-axis view is providing important mechanistic insights into when and why these hormones may work together to influence behavior, such as under conditions of challenge (Mehta, Jones, & Josephs, 2008; Mehta & Josephs, 2010). Initially, ‘coupling’ was theorized to be observed primarily in adolescents who may need to maintain capacity to activate androgens even under stress (Ruttle et al, 2015; Susman et al, 2017), yet positive coupling has also been observed in adults (Bobadilla, Asberg, Johnson, & Shirtcliff, 2014, Harden et al, 2016). Marceau and colleagues (2014) examined coupling in response to three stressors and other research has examined multiple stress biomarkers (Bedgood, Boggiano, & Turan, 2014; Chatterton, Vogelsong, Hudgens, & 1997; Eatough et al, 2009; Knight & Mehta, 2017, Turan, Tackett, Lechtreck, & Browning, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This explanation can also help to explain why we found a moderation effect for the AUCG only for male adolescents. Research shows that male adolescents generally have higher morning testosterone levels (Harden et al, ; Marceau, Ruttle, Shirtcliff, Essex, & Susman, ; Marceau, Ruttle, Shirtcliff, Hastings et al, ). Thus, perhaps higher testosterone levels among male adolescents drive more aggressive behaviors in reaction to the prior day experiences of victimization.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation can also help to explain why we found a moderation effect for the AUCG only for male adolescents. Research shows that male adolescents generally have higher morning testosterone levels (Harden et al, 2016;Marceau, Ruttle, Shirtcliff, Essex, & Susman, 2015;Marceau, Ruttle, Shirtcliff, Hastings et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ellison and Gray (2009) determined that cortisol and testosterone are implicated in the physiological stress response and noted that these hormones are tied to both individual and group learning. Previous research has found that acute stress is associated with increased testosterone (within individuals) and positive associations occur between salivary cortisol and testosterone, known as 'coupling' (Harden et al, 2016). Testosterone is also known to be associated with competition, where individuals who win competitions exhibit higher testosterone levels than those who lose (Booth, Shelley, Mazur, Tharp, & Kittok, 1989).…”
Section: Salivary Testosteronementioning
confidence: 99%